Design Interactive Coal Mining Layout Pop-up Book: An Educational Tool for Introducing Environmental Awareness to Children - Nurul Fitriyah Sulaeman; Khusnul Khotimah; Atin Nuryadin; Erna Sari; Ida Ayu Adinda Dhevi Pramesti; Ayu Ramadani Wandira; Anissa Widya Wati; Angelica May C. Rodriguez (Universitas Lambung Mangkurat, 2026)
Understanding the balance between energy production and environmental sustainability remains a challenge for young learners, particularly when addressing complex topics such as coal mining. This community service initiative aims to design, implement, and evaluate an interactive coal mining pop-up book as a developmentally appropriate learning medium to enhance elementary students’ environmental awareness. The activity was conducted using a Participatory Action Research (PAR) approach, involving stages of engagement, co-development, implementation, evaluation, and feedback. It included the design of 3D pop-up media, implementation through an interactive storytelling and demonstration session at Nido Primary School, and evaluation through Likert-scale questionnaires and observations. The findings indicate a notable improvement in students’ environmental awareness, with 87.0% of students expressing agreement on eco-centric and nature-responsibility aspects. Moderate levels of agreement were also observed in students’ understanding of coal-related concepts, indicating the development of conceptual comprehension. The pop-up book effectively supports learning through its visual and tactile features, which help students concretize abstract concepts in line with their cognitive development. Overall, this activity demonstrates that interactive and hands-on learning media can serve as an effective approach to introducing energy concepts while fostering early environmental awareness among elementary students.